Mass Spectrometry in Life Sciences and Clinical Laboratory 2021
DOI: 10.5772/intechopen.95335
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Peptides and Proteins in Illegally Distributed Products by MALDI-TOF-MS

Abstract: An analytical strategy based on matrix-assisted laser desorption/ionization (MALDI) time-of-flight (TOF) mass spectrometry (MS) for identification of peptides and proteins in illegally distributed products is presented. The identified compounds include human growth hormone (hGH), human somatoliberin, anti-obesity drug (AOD), growth hormone releasing peptides (GHRP-2 and GHRP-6), Glycine-GHRP-2 and Glycine-GHRP-6, ipamorelin, insulin aspart and porcine, delta sleep-inducing peptide (DSIP), thymosin β4, insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…11 In another study, from the analysis of illegally confiscated peptides and proteins, they also analyzed after trypsin digestion of Ac-Tβ4. 22 Other researchers also reported that LAP could break down the K-T bond of TB-500 (Ac-LKKTETQ) in in vitro experiment to generate Ac-LKK peptide metabolite. 18 Recently, we reported that the metabolite Ac-Tβ 1-14 was produced in vitro by enzymatic reaction in K-S bond (between positions 14 and 15 of Ac-Tβ4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 In another study, from the analysis of illegally confiscated peptides and proteins, they also analyzed after trypsin digestion of Ac-Tβ4. 22 Other researchers also reported that LAP could break down the K-T bond of TB-500 (Ac-LKKTETQ) in in vitro experiment to generate Ac-LKK peptide metabolite. 18 Recently, we reported that the metabolite Ac-Tβ 1-14 was produced in vitro by enzymatic reaction in K-S bond (between positions 14 and 15 of Ac-Tβ4).…”
Section: Discussionmentioning
confidence: 98%
“…Huang et al reported the presence of Ac‐Tβ4 in the wound by digesting wound tissues with trypsin for analysis with MALDI‐TOF MS and found the Ac‐Tβ 1–14 fragment because of a trypsin digestion of Ac‐Tβ4 11 . In another study, from the analysis of illegally confiscated peptides and proteins, they also analyzed after trypsin digestion of Ac‐Tβ4 22 . Other researchers also reported that LAP could break down the K–T bond of TB‐500 (Ac‐LKKTETQ) in in vitro experiment to generate Ac‐LKK peptide metabolite 18 .…”
Section: Discussionmentioning
confidence: 99%